Pedagogical Opportunities of Forming Professional and Cultural Skills in Students (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
In this article, the concept of professional and cultural, the fact that professional culture is of special importance for the formation of skills in students today, the moral image of students, Enriching their worldview and manners, educating them in a cultured manner, teaching them to work honestly, instilling a sense of humanity and patriotism in students, and preparing them for their chosen profession. knowledge about the need to educate a person who serves with loyalty is highlighted.